RESPON PEMBERIAN ZAT PENGATUR TUMBUH ATONIK DAN PUPUK NPK MUTIARA TERHADAP PERTUMBUHAN VEGETATIF PADA TAHAPAN PRE-NURSERY TANAMAN KELAPA SAWIT (Elaeis guenensis Jacq) - Dalimunthe, Badrul Ainy (Agros Journal of Agriculture Science, 2024)
One of the oil palm pre-nursery seeding techniques that complies with standards is the use of growth regulators and fertilizers during the seeding process. The aim of this research was to determine the effect of giving Atonik ZPT and Mutiara NPK Fertilizer on the vegetative growth of oil palm seedlings at the pre-nursery stage and their interactions. The research was carried out at the experimental field of the Agrotechnology Study Program, Faculty of Science and Technology, Labuhanbatu University. The design used was a factorial Randomized Block Design (RAK) with two factors, namely the factor of giving Atonik ZPT and giving NPK Mutiara fertilizer with 12 treatment combinations: Z0 (control), Z1 (2 g/polybag), Z2 (4 g/polybag). Mutiara NPK fertilizer was given at 4 levels: P0 (control), P1 (2 ml/liter of water, P2 (4 ml/liter of water), P3 (6 ml/liter of water). The parameters observed were the increase in plant height (cm), diameter stem (mm), number of leaves (strands), and leaf area (cm). The results showed that: (a) administration of NPK Mutiara had a significant effect on leaf area, but had no significant effect on plant height, number of leaves, and stem diameter; (b) giving Atonik ZPT had a significant effect on plant height and leaf area, but had no real effect on number of leaves and stem diameter; (c) there was no interaction between the two treatments for all parameters observed; (d) the best combination was the treatment given NPK Pearls 4 g/polybag with ZPT Atonik 6 cc/liter of water. Keywords : palm oil, pre-nursery, ZPT, NPK fertilizer INTISARISalah satu teknik pembibitan pre-nursery kelapa sawit yang sesuai standar adalah penggunaan zat pengatur tumbuh dan pupuk selama proses pembibitan. Tujuan penelitian ini adalah untuk mengetahui pengaruh pemberian ZPT Atonik dan Pupuk NPK Mutiara terhadap pertumbuhan vegetatif bibit kelapa sawit pada tahapan pre–nursery serta interaksinya. Penelitian dilaksanakan di Lahan percobaan Program Studi Agroteknologi, Fakultas Sains dan Teknologi, Universitas Labuhanbatu. Rancangan yang digunakan adalah Rancangan Acak Kelompok (RAK) faktorial dengan dua faktor, yaitu faktor pemberian ZPT Atonik dan pemberian pupuk NPK Mutiara dengan 12 kombinasi perlakuan: Z0 (kontrol), Z1 (2 g/polibag), Z2 (4 g/polibag). Pemberian pupuk NPK Mutiara dengan 4 taraf: P0 (kontrol), P1 (2 ml/liter air, P2 (4 ml/liter air, P3 (6 ml/liter air). Parameter yang diamati adalah pertambahan tinggi tanaman (cm), diameter batang (mm), jumlah daun (helai), dan luas daun (cm). Hasil menunjukkan bahwa: (a) pemberian NPK Mutiara berpengaruh nyata terhadap luas daun, tetapi tidak berpengaruh nyata terhadap tinggi tanaman, jumlah daun, dan diameter batang; (b) pemberian ZPT Atonik berpengaruh nyata terhadap tinggi tanaman dan luas daun, tetapi tidak berpengaruh nyata terhadap jumlah daun dan diameter batang; (c) tidak ada interaksi pada kedua perlakuan terhadap semua perameter yang diamati; (d) kombinasi terbaik adalah pada perlakuan pemberian NPK Mutiara 4 g/polibag dengan ZPT Atonik 6 cc/liter air. Kata kunci : kelapa sawit, pre-nursery, ZPT, pupuk NPK